2021
DOI: 10.3389/fcell.2021.730042
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Therapies in Hearing Loss

Abstract: In recent years, neural stem cell transplantation has received widespread attention as a new treatment method for supplementing specific cells damaged by disease, such as neurodegenerative diseases. A number of studies have proved that the transplantation of neural stem cells in multiple organs has an important therapeutic effect on activation and regeneration of cells, and restore damaged neurons. This article describes the methods for inducing the differentiation of endogenous and exogenous stem cells, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Thus, an effective way to treat hearing loss is to regenerate or repair damaged cells in the inner ear. During the past decade, gene therapy and neural stem cell therapy have emerged as promising treatment strategies for hearing loss ( He et al, 2021 ; Nourbakhsh et al, 2021 ; Qi et al, 2022 ). One major challenge of gene therapy is effectively delivering genes to target cells, and at present, the delivery vectors contain two types: viral and non-viral.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an effective way to treat hearing loss is to regenerate or repair damaged cells in the inner ear. During the past decade, gene therapy and neural stem cell therapy have emerged as promising treatment strategies for hearing loss ( He et al, 2021 ; Nourbakhsh et al, 2021 ; Qi et al, 2022 ). One major challenge of gene therapy is effectively delivering genes to target cells, and at present, the delivery vectors contain two types: viral and non-viral.…”
Section: Discussionmentioning
confidence: 99%
“…Among viral vectors, the Adeno-associated virus (AAV) vector is suitable for the treatment of hearing loss with a number of AAV serotypes have been developed, such as AAV1( Akil et al, 2012 ), AAV-ie ( Tan et al, 2019 ; Tao et al, 2022 ), AAV9-PHP.B ( Taiber et al, 2021 ), etc. In addition to gene therapy, using stem cells to induce differentiation to regenerate or repair damaged cells in the inner ear is regarded as the most feasible treatment ( He et al, 2021 ). There are usually two routes of research: the transplantation of exogenous stem cells and their subsequent differentiation in the damaged tissue and the genetic modification of endogenous cells to promote their transdifferentiation potential ( de Felipe et al, 2011 ; Duran-Alonso, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various other in vitro experiments have newly demonstrated that the cGMP-dependent atrial natriuretic peptide (ANP) and the permissive environment created by novel silicon micro-pillar substrates (MPS) could facilitate the survival and growth of SGNs (Mattotti et al, 2015;Sun et al, 2020). Through in vivo experiments, mesenchymal stem cells (Maharajan et al, 2021), valproic acid (VPA; 2-propylpentanoic acid) with growth factors (Wakizono et al, 2021), as well as neural stem cells (He et al, 2021) have been found to be beneficial for SGN growth.…”
Section: Treatment Of New Materials In Sensorineural Hearing Lossmentioning
confidence: 99%
“…Studies have shown that because SGNs cannot regenerate, the loss of cochlear signals can lead to irreversible hearing damage ( Liu et al, 2019a ; Ding et al, 2020 ). Thus, recently many studies have focusd on the regeneration of SGN via neural stem cells ( Guo et al, 2021b ; He Z. et al, 2021 ). Spiral ganglion Schwann cells (SGSs) are glial cells responsible for myelination in the peripheral nervous system ( Wise et al, 2017 ; Meas et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%